Research and Application of Reservoir Safety Monitoring System for Intelligent Water Conservancy. Issue 1 (March 2020) - Li, Xiuwen; Zhang, Shunfu; Wu, Hao; Tian, Dongcheng
Abstract: Safety monitoring systems are an important part of intelligent water conservancy projects. Based on the overall scheme requirements of intelligent water conservancy in the new era, we analyzed the new requirements of the current safety monitoring system. Intelligent perception, infrastructure, data resources, intelligent analysis and application display of reservoir safety monitoring system under the background of intelligent water conservancy are described respectively. Combined with the exploration of the intelligent safety monitoring system of Hekou Village reservoir, the functions of the system are introduced for further improvement. References and suggestions are provided for the construction of safety monitoring systems for intelligent water conservancy projects.